ANALISIS TERHADAP SENGKETA TANAH TERKAIT PENERBITAN SERTIPIKAT HAK GUNA BANGUNAN NOMOR 2849 (STUDI KASUS PUTUSAN MAHKAMAH AGUNG NOMOR 496/K/TUN/2017) - Evani Sugiharto; Hasni . (Jurnal Hukum Adigama, 2018)
Agrarian Law is overall legal provisions, both written and unwritten, which all of that have the same set of objectsthat is as legal institutions and as a concrete legal relationship, public and private aspect, which can be arranged and studied systematically. In agrarian section, in order to deal with concrete case, granting of legal security can’t be realized only with the availability of legal instruments. Land registration is required which will result certificate as a strong sign of land title. Lack of awareness in the importance of land registration activities and uncertainty over the grounds of the rights to the land owned.the problem in thiswritting ishow the implementation of Building Rights Title provition number 2849 according to the data from plaintiff and defendant over ground subject are already in accordance with legal provisions? The research method used is normative legal research method that comes from primary, secondary, and supported by interview with related experts, which is analyzed qualitatively. The result is Head of South Jakarta Land Officer who issued a Decree on Granting of Land Rights on December 5, 2013 number 991 not in accordance with the procedure in article 26 section 1 and article 28 section 1,3 Government Ordinance number 24/1997 because it has been issued 7 days prior to the end of the announcement period, so there are procedural defect in the Building Rights Title number 2849/Cilandak Barat.